Recipient risk factors for acute cellular rejection after orthotopic liver transplant ‐ a single‐center, retrospective study. (21st October 2020) - Choi, David; Liu, Mengyuan; Guttikonda, Dharani; Galen, Kelly; Guzman, Grace; Jeon, Hoonbae; Aloman, Costica
SUMMARY: The use of model for end‐stage liver disease (MELD) score for liver allocation has resulted in transplanting sicker patients. As such, it is unclear whether the risk factors and severity of acute cellular rejection (ACR) have changed. To identify ACR characteristics where average MELD score at transplant is higher than previously published studies. This is a single‐center, retrospective study designed to assess risk factors associated with ACR after adult orthotopic liver transplant (OLT) using a steroid sparing regimen. This study included 174 OLT patients transplanted from 2008 to 2013 at a single tertiary care center. Recipient demographics, preoperative clinical, and laboratory data were recorded for each transplant. Univariate and multivariate regression analyses were performed to identify variables that are significant predictors for ACR. The median MELD at transplantation was 29.5. The average time from transplant to ACR diagnosis was 283.9 days and a majority of ACR episodes were mild to moderate. Serum creatinine, primary sclerosing cholangitis etiology, and tacrolimus use were significant predictors for ACR ( P < 0.05). This study confirmed a change in timing and severity of ACR in the MELD era. Recipient characteristics may affect the risk for developing ACR and should be considered when managing immunosuppression.